Oriental Studies - D. V. Streltsov (Vestnik MGIMO-Universiteta)
The Department for the "administration of affairs with Asian nations" at College of Foreign Affairs was established on February 26, 1796 by the imperial decree and the school for Chinese, Manchu, Persian and Turkish languages translators was opened one year later. However, special training of the Russian diplomatic corps, dealing with the relations with Asian nations, was established only in the XIX century. In 1815 Lazarev Institute of Oriental Languages was founded. In 1823 Training Department of Oriental Languages at the Asian Department of the Foreign Ministry of the Russian Empire was established. The tradition was continued by the Soviet Russian Institute of Oriental Studies, which become a leading center for the training of specialists, necessary for most important public institutions and social organizations. Moscow Institute for Oriental Studies inherited traditions and rich library from Lazarev Institute. At the confluence of MGIMO and Moscow Institute of Oriental Studies in 1954 the library holdings were transferred to the MGIMO, they now form the basis of the rare fund of the university research library. Development of Oriental School MGIMO historically was influenced by the specifics of the traditional conglomerate of Oriental Sciences and ever increasing needs in the practical application of knowledge about the East. Of course, in addition to the Lazarev Institute other leading centers of domestic study of the East made a considerable impact on the development of Oriental Studies at MGIMO. St. Petersburg (Leningrad) University and the University of Kazan are the most prominent ones, where the Oriental Studies tradition is rooted in the XIX century. Evacuation of many prominent representatives of the Moscow and Leningrad school of Oriental Studies during the Great Patriotic War to Kazan and Central Asia gave new impetus to oriental studies at universities in these regions.